Pregled učinkovin brez recepta in prehranskih dopolnil za bolezni centralnega živčnega sistema - Janeš, Damjan (Farmacevtski vestnik, 2008)
Due to longer life, neurodegenerative disorders like Alzheimer's and Parkinson's disease have become a major health problem of senior population. The situation is very serious, since no treatment up to date is succesful in changing course or stopping the disease. The major reason for this is limited knowledge of the causes for diseases. Due to limited success of synthetic drugs, the interest in alternative medicine, especially fitotherapy has been constantly increasing. This article is a review of clinically tested and traditionally used herbs, herbal drugs, extracts, isolated compunds and food supplemends that have been used for prevention and treatment of neurodegeneretive diseases.
Keywords: Alzheimerjeva bolezen; fitoterapija; naravna zdravila; Parkinsonova bolezen